THE EFFECT OF LAVENDER AROMATHERAPY ON LEVELS PAIN OF LABOR WHEN I PHASE ACTIVE - Eka Fadilla, Nur; Norhapifah, Hestri (Jurnal Kesehatan, 2024)
Background: 80% of women describe labour pain as very severe and unbearable pain. Physiologically, labour pain will arise longer and more frequently, this will make the mother feel restless and anxious which causes an increase in excessive catecholamines and steroid hormones and causes uterine smooth muscle tension, making pain stimulation more intense. Lavender aromatherapy contains linalool, linalyl acetate and 1,8- cincole which can relax and quickly relax tension in muscles. Objective: To determine the effect of lavender aromatherapy on the level of labour pain in the active phase of the first stage of labour at RSIA Asy-Syfa Sangatta. Methods: This type of research is pre-experimental with one group pretest-posttest design by purposive sampling. The respondents in this study were 26 mothers who gave birth at RSIA Asy-Syfa Sangatta. The instrument uses a numerical rating scale (NRS) observation sheet and lavender aromatherapy SOP. Data were analyzed by Wilcoxon Signed Rank Test. Results: Of 26 respondents, most experienced severe pain as many as 21 people (80.8%) and after giving lavender aromatherapy 23 people (88.5%) experienced severe pain, 3 people (11.5) experienced severe pain. Conclusion: From this study, it was obtained a value of < 0.001 which means that there is an effect of lavender aromatherapy on the level of labour pain in the active phase of the first stage of RSIA Asy-syfa Sangatta.